Co‐administration of probiotic and vitamin D significantly improves cognitive function in schizophrenic patients: A double‐blinded randomized controlled trial - Aida Mohammadi; Gita Sadighi; Ali Nazeri Astaneh; Maryam Tajabadi‐Ebrahimi; Tahereh Dejam (Wiley, 2024)
Abstract Aim Manipulation of the intestinal microbiome and supplying vitamin D can attenuate psychiatric symptoms in schizophrenic patients. The current study tried to evaluate the effects of probiotic/vitamin D supplementation on the cognitive function and disease severity of schizophrenic patients. Methods In the present study, 70 patients (aged 18-65) with schizophrenia were recruited. Participants were randomly allocated to the placebo (n = 35) and intervention (probiotic supplements+400 IU vitamin D, n = 35) groups. Severity of disease and cognitive function (primary outcomes) were evaluated by Positive and Negative Syndrome Scale (PANSS) and Montreal Cognitive Assessment (MoCA) tests, respectively. Moreover, lipid profile, body mass index (BMI), gastrointestinal (GI) problems, serum C‐reactive protein (CRP), and erythrocyte sedimentation rate (ESR) were evaluated as secondary outcomes. Results A total of 69 patients completed the study. The MoCA score was increased by 1.96 units in the probiotic‐containing supplement group compared to the placebo (p = 0.004). Also, the percentage of subjects with MoCA score ≥ 26 rose significantly in the intervention group (p = 0.031). Moreover, TC (p = 0.011), FBS (p = 0.009), and CRP (p < 0.001) significantly decreased in the supplement group compared to the placebo. Although the probiotic supplement reduced PANSS score by 2.82 units, the difference between the study groups was not statistically significant (p = 0.247). Conclusion Co‐administration of probiotics and vitamin D has beneficial effects on the improvement of cognitive function in schizophrenic patients.